Aerobic fitness change with time in children with congenital heart disease: A retrospective controlled cohort study. (15th January 2023) - Gavotto, Arthur; Ladeveze, Manon; Avesani, Martina; Huguet, Helena; Guillaumont, Sophie; Picot, Marie-Christine; Requirand, Anne; Matecki, Stefan; Amedro, Pascal
Abstract: Background: To evaluate the change in aerobic fitness (VO2max ), measured by cardio-pulmonary exercise test (CPET), in children with congenital heart disease (CHD), compared to matched healthy controls, and identify predictors of VO2max change with time in this specific population. Method: This longitudinal retrospective multicentre cohort study was carried out from 2010 to 2020. We included CHD paediatric patients from the cohort of a previous cross-sectional study, who had a second CPET at least 1 year after the first one, during their follow-up. Results: We included 936 children, 296 in the CHD group and 640 controls. Mean time between baseline and final CPET was 4.4 ± 1.7 years. After matching on age and gender and adjustment for age and BMI, the mean VO2max group difference was 10.5% ± 1.0% of percent-predict VO2max at baseline and increased to 19.1% ± 1.3% at final assessment. In the CHD group, the proportion of children with impaired aerobic fitness was significantly higher at final than at baseline CPET assessment (51.4% vs 20.3%; P < 0.01 ). The mean annual VO2max decrease was significantly worse in the CHD group than in controls (−1.88% ± 0.19% of percent-predict VO2max /year vs. -0.44% ± 0.27% of percent-predict VO2max /year, P < 0.01, respectively). In multivariate analyse, male gender, a high initial VO2max, a high BMI, and the number of cardiac surgical procedures ≥2, were predictors of the VO2max decrease with time. Conclusion: The VO2max decrease with time is more pronounced in children with CHD compared to healthy matched controls. This study highlighted the importance of serial CPET assessment in children with CHD. Trial registration NCT04815577. Highlights: VO2max decrease with time is more pronounced in children with CHD. Predictors of VO2max decrease: gender, a high initial VO2max, BMI, surgeries ≥2. Serial CPETs are important to assess children with CHD.